Partial Monosomy 21 Mirrors Gene Expression of Trisomy 21 in a Patient-Derived Neuroepithelial Stem Cell Model - Schuy, Jakob; Eisfeldt, Jesper; Pettersson, Maria; Shahrokhshahi, Niloofar; Moslem, Mohsen; Nilsson, Daniel; Dahl, Niklas; Shahsavani, Mansoureh; Falk, Anna; Lindstrand, Anna (Frontiers in Genetics, 2022)
Induced pluripotent stem cells (iPSCs) from patients are an attractive disease model to study tissues with poor accessibility such as the brain. Using this approach, we and others have shown that trisomy 21 results in genome-wide transcriptional dysregulations. The effects of loss of genes on chromosome 21 is much less characterized. Here, we use patient-derived neural cells from an individual with neurodevelopmental delay and a ring chromosome 21 with two deletions spanning 3.8 Mb at the terminal end of 21q22.3, containing 60 protein-coding genes. To investigate the molecular perturbations of the partial monosomy on neural cells, we established patient-derived iPSCs from fibroblasts retaining the ring chromosome 21, and we then induced iPSCs into neuroepithelial stem cells (NESCs). RNA-Seq analysis of NESCs with the ring chromosome revealed downregulation of 18 genes within the deleted region together with global transcriptomic dysregulations when compared to euploid NESCs. Since the deletions on chromosome 21 represent a genetic “contrary” to trisomy of the corresponding region, we further compared the dysregulated transcriptomic profile in with that of two NESC lines with trisomy 21. The analysis revealed opposed expression changes for 23 genes on chromosome 21 as well as 149 non-chromosome 21 genes. Taken together, our results bring insights into the effects on the global and chromosome 21 specific gene expression from a partial monosomy of chromosome 21qter during early neuronal differentiation.